A Survey on Abandoned Objects Detection from CCTV Surveillance - Saluky Saluky (ITEJ (Information Technology Engineering Journals), 2020)
Computer Vision is an important and challenging area of ​​research in image processing applied to analytical video. Image data comes from CCTV surveillance which is spread in public places owned by the government, private sector and the public. Supervision is carried out to monitor anomalies in the surrounding environment such as abandoned objects, crowds, theft and others. An abandoned object is one of the anomalies that is important to monitor because it can be categorized as a danger and can also prevent theft of the object left behind, therefore automatic monitoring is needed to prevent adverse events from occurring. In the last decade, a number of publications have been presented in the field of intelligent visual surveillance to detect abandoned objects (AOD). In this paper, we present a state-of-the-art showing the overall progress of the detection of objects that were abandoned or removed from surveillance video in recent years. We include a brief introduction to the detection of abandoned objects with their problems and challenges. The aim of this paper is to provide a review of the literature in the field of recognition of abandoned objects of visual surveillance systems with a general framework for researchers in this field.